Chapter The Gospel according to Mark in two Latin Mixed-text Manuscripts - Houghton, H. A. G. (Vetus Latina, 2016)
Two late eighth-century Latin gospel books have recently been identified as witnesses to the pre-Vulgate text of the Gospel according to John. In this article, their text of Mark is analysed and shown also to contain significant Old Latin material notwithstanding their general affiliation to the Vulgate. VL 11A (Würzburg, Universitätsbibliothek M.p.th.f. 67) has an unaltered Old Latin portion between Mark 10:30 and 11:5 and earlier readings throughout the manuscript. There are a number of unique or poorly-attested variants, including de publico in 7:4 and cum omni sollicitudine in Mark 14:44 which may give some clues about the origin of the text. VL 9A (St Petersburg, National Library of Russia F.v.I.8) has a mixed text with a significant proportion of Old Latin readings in Mark 10-14. Some of these are only paralleled by VL 1 (Codex Bobiensis) and represent a very early Latin version. In certain introductions to direct speech, this is the only Latin witness which corresponds to the earliest Greek form of text. It is also suggested that the Durham Gospels (or a closely related manuscript) may have been used to adjust VL 9A towards the Vulgate. A critical apparatus is provided for Mark in each manuscript.